Disposal of expired and unused medications: a consumer behavior survey in São Mateus/ES - Balista, Wagner Cezário; Chaves, Gisele de Lorena Diniz; Sales, Ramiles; Lobo, Ludimila de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Improper disposal of expired and unused medications in possession of the population causes severe impacts on the environment and public health. Therefore, the objective of this study was to evaluate the population’s behavior in relation to the disposal of this waste. For this, a survey research was conducted in the municipality of São Mateus - ES, structured by a questionnaire to 400 people, to ensure a statistically significant sample. With the results and help of Action, statistical supplement of Excel, were performed statistical tests to verify the existence of relationship between the variables of interest search. It was found that 86.8% of consumers verify the validity of medicines, but 84% do not receive guidance on the correct disposal of expired medications and unused. Consequently, 81.3% of respondents perform the incorrect disposal of this waste. Statistical analyzes showed that consumers in the age group 46-55 years as well as respondents with 2nd degree or university degree, are those correctly discard expired medications and unused in greater proportion. The results point to the need for effectiveness in implementing the responsibilities set out in legislation and in its inspection and investment in continuous programs for environmental education.